The treatment of knee cartilage lesions: state of the art - Talesa, Giuseppe; Manfreda, Francesco; Pace, Valerio; Ceccarini, Paolo; Antinolfi, Pierluigi; Rinonapoli, Giuseppe; Caraffa, Auro (Acta Biomedica Atenei Parmensis, 2022)
The management and repair of knee cartilage lesions currently represents a challenge for the orthopaedic surgeon. Identifiable causes are the characteristics of the involved tissues themselves and the presence of poor vascularization, which is responsible for overall reduced repair capacity.The literature reports three types of cartilage lesions’ treatment modalities: chondroprotection, chondroreparation and chondrogeneration. The preference for one or the other therapeutic option depends on the pattern of the lesion and the clinical conditions of the patient.Each treatment technique is distinguished by the quality of the restorative tissue that is generated. In particular, the chondrorigeneration represents the last frontier of regenerative medicine, as it aims at the complete restoration of natural cartilage. However, the most recent literature documents good results only in the short and medium terms.In recent years the optimization of chondroregeneration outcomes is based on the modification of the scaffolds and the search for new chondrocyte sources, in order to guarantee satisfactory long-term results.